Strategi Pengembangan Potensi Pariwisata Di Desa Prongil Julu Kecamatan Tinada Kabupaten Pakpak Bharat - Restu Samosir; Albiner Siagian; Harisan Boni Firmando; Mery Silalahi; Yulia K.S Sitepu (Lembaga Pengembangan Kinerja Dosen, 2023)
The purpose of this study is to determine the strategy for developing tourism potential of Prongil Julu village, Tinada district, Pakpak Bharat district. This study uses qualitative research methods and uses SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis with three informants. The results of this study depict that developing tourism potential in Prongil Julu village has several advantages such as fresh air, cultural attractions, quite complete facilities, hospitality of people and entrance to the capital of Pakpak Bharat regent. However, there are also weaknesses such as underdeveloped infrastructure, lack of tourism promotion as well as lack of public interest and attention towards tourism. There are also opportunities to develop tourism through community tourism training, partnerships with the private sector and leveraging the benefits of Lae Mbilulu Falls to attract tourists. However, threats such as competition with destinations other than Prongil Julu Village and environmental damage also need attention. Based on these SWOT results, the author proposes a number of strategies to develop tourism potential such as infrastructure development, increased tourism promotion, tourism product development and cooperation with the private sector and Pakpak Bharat District Tourism Board. It is hoped that this strategy can help Prongil Julu Village maximize its tourism potential for economic growth and regional development.